Magnetic Door Lock System - Sharifuddin, Muhammad Syafiq; Ab Aziz, Ashraf Zulfadhli (2016)
Security is needed everywhere nowadays, most people has already adopted this idea and have secured their homes from intruders or robbers by using a simple lock and key. However, the lock can be easily lock picked or simply broken with a blunt object. This leaves the belongings of the owners prone to being taken or sometimes, depending on whether the owners are home or not, could be of a risk to their own lives. The lock also could trouble the owners as they would have to bring their key everywhere and if the key is lost, the owners would have to destroy their door to gain access to their own home. Hence, this project, the Magnetic Door Lock System has been designed to overcome the problems that arise and many more.